Reprogrammed Cell‐based Therapy for Liver Disease: From Lab to Clinic - Amir Mehdizadeh; Masoud Darabi (Journal of Renal and Hepatic Disorders)
A large number of patients are affected by liver dysfunction worldwide. Liver transplantation is the only efficient treatment in a variety of enduring liver disorders including inherent and end-stage liver diseases. The generation of human functional hepatocytes in high quantities for liver cell therapy is an important goal for ongoing therapies in regenerative medicine. Reprogrammed cells are considered as a promising and unlimited source of hepatocytes, mainly because of their expected lack of immunogenicity and minimized ethical concerns in clinical applications. Despite gained advances in the reprogramming of somatic cells to functional hepatocytes in vitro, production of primary adult hepatocytes that can proliferate in vivo still remains inaccessible. As part of efforts toward translation of cell reprogramming science into clinical practice, more careful cell selection strategies should be integrated into improvement of dedifferentiation and redifferentiation protocols, especially in precision medicine where gene correction is needed. Furthermore, advances in cellular reprogramming highlight the need for developing and evaluating novel standards addressing clinical research interests in this field.